Principal’s transformational leadership as a catalyst for teacher performance improvement in an Indonesian elementary school - Sandi Aditya; Anwar Novianto; Lantip Diat Prasojo (Jurnal Penelitian Ilmu Pendidikan, 2025)
This study analyzes how a school principal’s transformational leadership improves teacher performance at an elementary school in the Special Region of Yogyakarta, Indonesia. The research is grounded in the premise that teacher performance is critical to educational quality and that principals play a strategic role in guiding teaching and learning. A qualitative case study design was employed, involving the principal and teachers as participants, to gain an in-depth understanding of leadership strategies. Data were collected through in-depth interviews, non-participant observations, and document analysis, with methodological triangulation enhancing data validity. The principal was found to consistently practice all four dimensions of transformational leadership (Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration). Through these practices, the principal served as a disciplined role model, clearly articulated an inspiring vision, fostered innovation via professional development, and provided personalized support to teachers. As a result, teachers’ motivation, commitment, and performance showed significant improvement, leading to higher instructional quality and better student outcomes. These findings provide empirical evidence of the effectiveness of transformational leadership in the primary education context, underscoring the crucial role of principals in creating collaborative, innovative, and quality-oriented school environments.